Photocatalytic enantioselective α-aminoalkylation of acyclic imine derivatives by a chiral copper catalyst - Bowen Han (Nature Portfolio, 2019)
Copper-based asymmetric photocatalysis has great synthetic potential, however it has been rarely exploited due to challenges inherent to such systems. Here, a chiral bisoxazoline copper catalyst is involved in a SET process, photoredox catalysis, Lewis acid activation and asymmetric induction to construct chiral vicinal diamines.